Doing the Impossible: The Limits of Schooling, the Power of Poverty. Issue 1 (September 2017) - Payne, Charles M.; Ortiz, Cristina M.
The idea that schools can have little influence on children coming from poor homes and neighborhoods is often attributed to the 1966 Coleman Report. At one time, this position was clearly favored by conservatives seeking to minimize public investments; more recently, it has been embraced by progressives arguing to increase public investments in poor children. In either form, arguments about the inability of schools to effectively speak to the needs of poor students are often poorly specified and are increasingly in tension with the best available evidence. No matter how well-intentioned they are, these arguments may inadvertently reinforce some very problematic ideas about the potential impact of schools on the academic performance of disadvantaged youngsters. We argue that while the power of poverty to stunt growth is undeniable, we have to be more willing to learn from contemporary evidence that suggests schooling can significantly mitigate the negative effects of poverty.